Histopathological changes in epithelium of hair follicles and acrosyringium caused by measles in child, - Monique Freire Santana; Luiz Carlos de Lima Ferreira; Joao Gabriel Nogueira de Oliveira; Fábio Francesconi (Sociedade Brasileira de Dermatologia, 2020)
Abstract Some epidermal alterations in measles has been described, such as keratinocytes apoptotic, parakeratosis, giant-cell formation, intranuclear and cytoplasmic inclusions, dyskeratosis, spongiosis, and intracellular edema. The authors report for the first time in human a case of measles with the presence of multinucleated giant cells in the hair follicle and dyskeratosis in acrosyringium.